Animasi “Keluarga Aman” Sebagai Media Sosialisasi Pencegahan Penularan COVID-19 - Suliswaningsih Suliswaningsih; Achmad Masruri; Ganang Eko Saputro; Anugerah Bagus Wijaya; Chyntia Raras Ajeng Widiawati (Infotekmesin, 2023)
Adaptation to new habits (new normal) must be implemented considering that people must continue their activities amidst the outbreak of Covid-19 transmission cases. Apart from the government and community organizations, awareness of prevention must be carried out by each individual even though they have been vaccinated. The purpose of this research is to create a 2D animation to socialize the application of the 5M health protocol used to prevent widespread transmission of Covid-19. The process of creating a 2D animation titled "Safe Family" is carried out in three stages. First, the pre-production stage includes defining ideas and concepts, writing scripts, storyboards, and audio recording. The production stage includes character creation, moving animation, inputting sound, and initial rendering (alpha test). The third step is the post-production stage, namely the final rendering. and evaluation (beta test). The results of the alpha test show the suitability of the idea, storyboard, and final rendering results. In addition, the results of beta testing show that on average 93.4% of respondents considered the 2D animation titled "Safe Families" to be appropriate for use as social media to prevent Covid-19 communication.